Educated by initiative : the effects of direct democracy on citizens and political organizations in the American states - Smith, Daniel A., 1966-; Tolbert, Caroline J. (Ann Arbor : University of Michigan Press, 2004)
Educated by Initiative moves beyond previous evaluations of public policy to emphasize the educational importance of the initiative process itself. Since a majority of ballots ultimately fail or get overturned by the courts, Smith and Tolbert suggest that the educational consequences of initiative voting may be more important than the outcomes of the ballots themselves. The result is a fascinating and thoroughly-researched book about how direct democracy teaches citizens about politics, voting, civic engagement and the influence of special interests and political parties. Designed to be accessible to anyone interested in the future of American democracy, the book includes boxes (titled "What Matters") that succinctly summarize the authors' data into easily readable analyses
The Progressive Era vision : instrumental and educative justifications of direct democracy -- The education of citizens : voting -- The education of citizens : civic engagement -- The education of citizens : confidence in government -- The education of special interests -- The education of political parties -- The educative possibilities and limitations of citizen lawmaking.
Includes bibliographical references (pages 201-217) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Political participation -- United States -- States; Referendum -- United States -- States; Direct democracy -- United States -- States; Progressivism (United States politics); Participation politique -- États-Unis -- États.; Référendum -- États-Unis -- États.; Démocratie directe -- États-Unis -- États.; Progressisme -- États-Unis.; POLITICAL SCIENCE -- Government -- Legislative Branch; LAW -- General; Political participation -- U.S. states; Progressivism (United States politics); Referendum -- U.S. states; United States; Direkte Demokratie; Progressismus; Politische Beteiligung; Bundesstaaten; Volksabstimmung; USA; Electronic books